2015
DOI: 10.1093/geronb/gbv039
|View full text |Cite
|
Sign up to set email alerts
|

Age Effects in Adaptive Criterion Learning

Abstract: These findings evidence labile adaptive criteria placement and criteria shifting with age. However, age-related tendencies toward conservative response biases may limit the extent to which criteria can be shifted in a lenient direction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 67 publications
2
11
0
Order By: Relevance
“…This age-attributed valence could arise from general age-related performance or criterion biases in decision-making: many older participants express wanting to “do well” in experiments, and responses can tend toward the conservative with age (e.g., Ratcliff et al, 2006; Cassidy and Gutchess, 2015). However, the two-alternative forced-choice procedure used here is criterion-independent (Green and Swets, 1974) and therefore not subject to age-associated criterion biases.…”
Section: Discussionmentioning
confidence: 99%
“…This age-attributed valence could arise from general age-related performance or criterion biases in decision-making: many older participants express wanting to “do well” in experiments, and responses can tend toward the conservative with age (e.g., Ratcliff et al, 2006; Cassidy and Gutchess, 2015). However, the two-alternative forced-choice procedure used here is criterion-independent (Green and Swets, 1974) and therefore not subject to age-associated criterion biases.…”
Section: Discussionmentioning
confidence: 99%
“…What are the characteristics of a good criterion shifter? Whereas some studies have suggested factors that may predict criterion placement and shifting, including age (Cassidy & Gutchess, 2015), sensitivity to the strength of one’s own memories (Selmeczy & Dobbins, 2013), and social cues (Cassidy, Dubé, & Gutchess, 2015), what may be more notable are all the factors that do not predict criterion shifting. These include measures of intelligence and executive-functioning skills such as working memory capacity and task-switching ability, as reported by Aminoff and colleagues (2012) in a large-scale study of individual differences that included 95 subjects.…”
Section: The Willingness To Criterion Shiftmentioning
confidence: 99%
“…In contrast, a more conservation response criterion results in a higher likelihood of reporting that a target is absent. Adaptive response criteria have been observed among older adults in memory tasks (Baron & Surdy, 1990; Cassidy & Gutchess, 2015; Marquié & Baracat, 2000; Pendergrass, Olfman, Schmalstig, Seder, & Light, 2012) and auditory perception (Craik, 1969). In driving, adapting response criteria according to the demand and context of the target detection task may benefit older drivers in detecting road hazards.…”
Section: Introductionmentioning
confidence: 99%